Improved conversion of carbon dioxide to methane via photohydrogenation using Gd2NiMnO6 with a dendritic fibrous architecture - Ping Yan; Dulong Feng; Qian Wan; Shulong Liu; Seyed Mohsen Sadeghzadeh (Scientific Reports)
Abstract The conversion of diluted CO₂ into high-energy fuels is increasingly central to renewable energy research. This study investigates the efficacy of a Gd₂NiMnO₆ dendritic nanofibrous (DNF) photocatalyst in transforming carbon dioxide to methane through photoreduction. Gd₂NiMnO₆ DNF was found to provide active adsorption sites and control the strand dimensions for metal groups, facilitating the chemical absorption of CO₂. The light-driven photoreduction of CO₂ to CH₄ through biomass valorization has become a sustainable focus area, with photocatalytic CO₂ reduction recognized as a key strategy to mitigate greenhouse gases and achieve carbon neutrality. However, designing active sites with enhanced selectivity and efficiency for CO₂ photoreduction remains challenging. Reducing carbon dioxide is especially crucial in the era of petroleum refineries. This work introduces a reusable, magnetically responsive nanocatalyst for the targeted light reduction of CO₂ to CH₄, utilizing eco-friendly methods, mild thermal conditions, ambient pressure, and sustainable dehydrating agents. This approach provides significant economic benefits and compatibility with functional groups, highlighting the potential of combining 3D nanoparticle structures with sustainable chemistry to create highly efficient catalytic systems for CO₂ to CH₄ conversion.